Electrochemical additive manufacturing (ECAM): A new approach to fabricate metal nanostructures. (2023) - Siddiqui, Hafsa; Singh, Netrapal; Katiyar, Diksha; Naidu, Palash; Mishra, Shivi; Chandra Prasad, Harish; Akram Khan, Mohd.; Ashiq, Mohammad; Sathish, N.; Kumar, Surender
Graphical abstract: Highlights: Electrochemical additive manufacturing (ECAM) was successfully used to fabricate the Ag-NPs SERS substrates. The Ag-NPs SERS substrates was successfully applied to the sensitive detection of Aspirin. Aspirin molecule can be detected up to 10 −8  M using ECAM printed Ag-NPs SERS substrates. Abstract: Nanoscale printing is growing rapidly as a feasible fabrication method for a wide range of applications, including electronics and nanooptics, sensors, nanorobots, and energy storage. In today's cutting-edge technologies, the constantly reducing dimension necessitates the production of complex conductive structures with nanometre resolution., ECAM methods can produce impurity-free metallic conductors with excellent electrical and mechanical properties; however, the true nanoscale resolution remains very challenging. Here, silver nanostructures are synthesized by an ECAM process and investigated as a substrate for surface-enhanced Raman scattering (SERS) detection of aspirin. Various characterizations such as XRD, TEM, HR-TEM, FE-SEM, EDX-mapping, optical, ultraviolet–visible, and Raman spectroscopy are used to analyse ECAM-printed nanostructured silver substrates. A remarkable enhancement factor of ∼ 10 7 is realized in the silver nanostructured substrates with the detected limit of 10 -8 mol. ECAM printed silver nanostructured substrates can thus be used as viable substrates for SERS applications.